Dampak Pemanfaatan Limbah Kotoran Sapi Terhadap Peningkatan Kesejahteraan Peternak Sapi di Desa Suntenjaya, Kabupaten Bandung Barat - Laila Asfari; Ade Yunita Mafruhat, S.E., M.SOC. SC (UNISBA Press, 2023)
Abstract Livestock waste is the by-product of a livestock business which contains potential for the agricultural industry if managed properly. The problem that exists in the livestock industry is the accumulation of waste so that it will have a negative impact on the surrounding environment. Utilization of cow manure can affect socio-economic welfare. The purpose of this study is to analyze the impact of using cow manure on the socio-economic welfare of farmers in Suntenjaya Village. The method used in this research is quantitative descriptive and the Wilcoxon Signed rank test analysis model. The data collection technique uses a questionnaire and the population is farmers in Suntenjaya Village. The results of this study indicate that the use of cow manure has 8 positive impacts which include on social welfare and 4 positive impacts on economic welfare. Utilization of cow dung waste from economic perspective, that its, breeders use it to become a product of economic value so as to be able to increase income, reduce fuelenergi expenditure, and open up new jobs, when viewed from a social perspekctive, namely increasing the culture of mutual cooperation among residents, reducing environmental pollution and increase farmer’s insight regarding the use of waste through counselling and outreach. Abstrak Limbah ternak merupakan hasil sisa dari suatu usaha peternakan yang memiliki kandungan yang potensial untuk industri pertanian apabila dikelola dengan baik.Permasalahan yang ada dalam industri peternakan yakni penumpukan limbah sehingga akan berdampak negatif terhadap lingkungan sekitar. Pemanfaatan limbah kotoran sapi mampu mempengaruhi kesejahteraan sosial ekonomi. Tujuan dari penelitian ini yaitu untuk menganalisis dampak dari pemanfaatan limbah kotoran sapi terhadap kesejahteraan sosial ekonomi peternak di Desa Suntenjaya. Metode yang digunakan dalam penelitian ini adalah deskirptif kuantitatif dan model analisis Wilcoxon Signed rank test. Teknik pengumpulan data menggunakna kuesioner dan populasi yaitu peternak di Desa Suntenjaya. Hasil dari penelitian ini menunjukkan bahwa pemanfaatan limbah kotoran sapi memberikan 8 dampak positif yang meliputi 4 dampak positif bagi kesejahteraan sosial dan 4 dampak positif bagi kesejahteraan ekonomi. Pemanfaatan limbah kotoran sapi dilihat dari segi ekonomi yaitu peternak memanfaatkan menjadi suatu produk bernilai ekonomis sehingga mampu meningkatkan pendapatan, mengurangi pengeluaran energi bahan bakar serta membuka lahan pekerjaan baru, apabila dilihat dari segi sosial yaitu meningkatkan budaya gotong royongantar warga, mengurangi pencemaran lingkungan serta meningkatkan wawasan peternak mengenai pemanfaatan limbah melalui penyuluhan dan sosialisasi.